COUNTER NARRATIVE OF ISLAMOPHOBIA: CRITICAL DISCOURSE ANALYSIS OF IMRAN KHAN’S SPEECHES - Anam Safarish; Amna Zahid Chaudhary; Ayesha Nawaz (International Journal of Contemporary Issues in Social Sciences, 2024)
This study employs a critical discourse analysis approach to analyze the counter-narrative of Islamophobia that Imran Khan put forth during his addresses at the United Nations Organization (UNO). The literature review examines current research on Islamophobia, counter-narratives, and the impact of political speech, establishing the basis for this study. This research tries to analyze the language tactics used by Khan to challenge existing narratives, preconceptions, and biases about Islam and Muslims on the world arena. The research focuses on comprehending how political speech might function as a deterrent to Islamophobia, specifically within international relations. The study aims to provide a comprehensive analysis of Khan’s talks, elucidating the intricacies of his language and its influence on creating the narrative landscape. The primary research examines how Imran Khan’s use of language and communication techniques contribute to the development of a narrative that opposes and challenges Islamophobia. The motivation for this research stems from the significance of political discourse in shaping global views and the need for detailed studies examining counter-narratives’ socio-cognitive aspects. The study has great importance due to its ability to enhance the comprehension of successful counter-narrative tactics against Islamophobia, therefore enriching both academic and policy discussions. The theoretical approach is based on Van Dijk’s socio-cognitive paradigm (2017), which allows for the examination of both the cognitive and social elements of speech. The study implements qualitative methodologies, namely critical discourse analysis, to thoroughly examine the linguistic characteristics of the speeches and their consequences. This study aims to enhance our knowledge of how political rhetoric may effectively combat Islamophobia and create a narrative that encourages global mutual understanding and tolerance.